Transethosomes: An Innovative Approach for Drug Delivery (Asian Journal of Pharmaceutics (AJP), 2023)
Since a few years ago, the delivery of drugs through the skin has gained popularity. By doing so, it gets aroundproblems with the oral route. Despite the fact that only a few pathways are as appealing as the transdermalroute, it is difficult to deliver drugs through the skin. Researchers have developed a technique that allows themedicine to be encapsulated into vesicles, which may then go deep into the layer of skin to reach the target spot.Consequently, bioactive agents can penetrate the skin more effectively. Liposomes, niosomes, transethosomes,and transferosomes are vesicular systems that frequently remain collected in the skin layers. Transethosomes canpass through multiple layers of skin because they have tiny particle sizes and can change the form of vesiclesmore easily than another vesicular system. Transethosomes allow the medicine to be conveniently delivered tothe target place. Ethanol, phospholipids, and an edge stimulator make up transethosomes. Transethosomes’ abilityto penetrate the skin is improved by ethanol and edge stimulators. It increases patient cooperation because it is anon-intrusive procedure. It also improves the effectiveness of drug entrapment. These vesicles can hold a widerange of medications, including pain relievers, antitumor medicines, steroids, proteins, and peptides.